PREDICTING EXTREME RETURNS AND PORTFOLIO MANAGEMENT IMPLICATIONS. (December 2013) - Fodor, Andy; Krieger, Kevin; Mauck, Nathan; Stevenson, Greg
Abstract We consider which readily observable characteristics of individual stocks may be used to forecast subsequent extreme price movements. We believe we are the first to explicitly consider the predictive influence of option implied volatility in such a framework, which we find to be an important indicator. However, after controlling for implied volatility levels, other factors, particularly firm age and size, continue to have additional predictive power of extreme returns. Furthermore, excluding predicted extreme return stocks leads to a portfolio that has lower risk (standard deviation of returns and lower beta) without sacrificing performance.